Improved Survival and Cure Rates With Concurrent Treatment for Multidrug-Resistant Tuberculosis–Human Immunodeficiency Virus Coinfection in South Africa. (26th December 2017) - Brust, James C M; Shah, N Sarita; Mlisana, Koleka; Moodley, Pravi; Allana, Salim; Campbell, Angela; Johnson, Brent A; Master, Iqbal; Mthiyane, Thuli; Lachman, Simlatha; Larkan, Lee-Megan; Ning, Yuming; et al.
Abstract : Coinfected participants treated concurrently for multidrug-resistant (MDR) tuberculosis and human immunodeficiency virus had survival similar to that of participants with MDR tuberculosis alone. Mortality was higher among patients whose CD4 count was persistently ≤100 cells/mm 3 . Abstract: Background: Mortality in multidrug-resistant (MDR) tuberculosis–human immunodeficiency virus (HIV) coinfection has historically been high, but most studies predated the availability of antiretroviral therapy (ART). We prospectively compared survival and treatment outcomes in MDR tuberculosis–HIV-coinfected patients on ART to those in patients with MDR tuberculosis alone. Methods: This observational study enrolled culture-confirmed MDR tuberculosis patients with and without HIV in South Africa between 2011 and 2013. Participants received standardized MDR tuberculosis and HIV regimens and were followed monthly for treatment response, adverse events, and adherence. The primary outcome was survival. Results: Among 206 participants, 150 were HIV infected, 131 (64%) were female, and the median age was 33 years (interquartile range [IQR], 26–41). Of the 191 participants with a final MDR tuberculosis outcome, 130 (73%) were cured or completed treatment, which did not differ by HIV status ( P = .50). After 2 years, CD4 count increased a median of 140 cells/mm 3 ( P = .005), and 64% had an undetectable HIV viral load. HIV-infected and HIV-uninfected participants had high rates of survival (86% and 94%, respectively; P = .34). The strongest risk factor for mortality was having a CD4 count ≤100 cells/mm 3 (adjusted hazards ratio, 15.6; 95% confidence interval, 4.4–55.6). Conclusions: Survival and treatment outcomes among MDR tuberculosis–HIV individuals receiving concurrent ART approached those of HIV-uninfected patients. The greatest risk of death was among HIV-infected individuals with CD4 counts ≤100 cells/mm 3 . These findings provide critical evidence to support concurrent treatment of MDR tuberculosis and HIV.